Pre-pandemic family resources and child self-regulation in children’s internalizing problems during COVID-19: a multi-level social-ecological framework for emotional resilience - Chen, Luxi; Yeung, Wei-Jun Jean (Frontiers in Psychology, 2023)
This study explored diverse protective factors in the family against children’s internalizing problems, and investigated the mediating pathways linking family-, parent- and child-level resources to children’s mental health, in the context of COVID-19. Our participants were a nationally representative sample of 2,619 children aged 3 to 6 (48.3% girls) and their primary caregivers (95.1% were mothers). Data were collected over two waves – before the outbreak of the COVID-19 pandemic (Wave 1) and during the second year of the pandemic (Wave 2). Primary caregivers completed measures of verbal cognitive ability, self-control, economic stress, positive and negative parental control, and other family characteristics in Wave 1. Children’s self-regulation was assessed by the Delay of Gratification task in Wave 1, and their internalizing problems were rated by their primary caregivers in both waves. Structural equation modeling was performed. Mediation analyses revealed that pre-pandemic parental resources (i.e., verbal cognitive ability, self-control, and low economic stress) predicted children’s fewer internalizing problems during the pandemic through more positive parental control (i.e., limit setting) and less negative parental control (i.e., harsh discipline). These mediating pathways remained significant after controlling for children’s pre-pandemic internalizing problems. Moreover, children’s self-regulation during early childhood was predicted by primary caregivers’ verbal cognitive ability, self-control, and positive parental control. Child self-regulation in Wave 1 further predicted a lower increase in internalizing problems from before to during the pandemic. In addition, among the covariates, parental education, family income, living with both parents, and having a live-in domestic helper(s) also protected children from aggravation of internalizing symptoms over time. Our findings underscore the importance of nurturing children’s emotional resilience under adverse and uncertain circumstances by boosting protective factors in children’s social-ecological system.